Qur'anic Parenting: Comparative Study of the Meaning of Surah Luqman Verses 12-19 in the Tafsir Ibn Kathir and Tafsir Fathu al-Qadir - Permatasari, Indah Gilang; Rhain, Ainur; Nugroho, Kharis; Nirwana, Andri; Dahliana, Yeti (Universitas Muhammadiyah Surakarta, 2023)
Having a child is a gift that must be accompanied by a duty of trust. Many Muslim families do not understand the concept of Islamic education in accordance with the Qur'an and Sunnah so that they are unable to educate children into a rabbani generation that is firm in ethics and morality. The purpose of this study is to find out the value of parents' education towards children by referring to the interpretation of Luqman's letter verses 12-19 by making a comparison between Ibn Katsir's tafsir and Fathu al-Qadir's Tafsir of Imam Asy-Syaukani. The methods used in this study are library research and comparative studies to explore the differences and similarities of interpretation of the two. Analysis is done on key aspects such as interpretation methods, historical context, and religious values considered important in understanding the verses. The source used is a direct reference to the mother books of Ibn Katsir and Fathu al-Qadir along with other references from articles and scientific journals related to the speech. The results of the study indicate that Ibn Katsir emphasized more on traditional aspects and religious values in the upbringing of children, while the Assy-Syaukani priest tended to incorporate social and humanitarian contexts in his understanding. This comparison provides an in-depth insight into the diversity of Islamic perspectives on parents' responsibilities in educating children, as well as their implications for modern educational practices.